2021
DOI: 10.1371/journal.pone.0254207
|View full text |Cite
|
Sign up to set email alerts
|

Processing of expressions by individuals with autistic traits: Empathy deficit or sensory hyper-reactivity?

Abstract: Individuals with autistic traits display impaired social interaction and communication in everyday life, but the underlying cognitive neural mechanisms remain very unclear and still remain controversial. The mind-blindness hypothesis suggests that social difficulties in individuals with autistic traits are caused by empathy impairment in individuals; however, the intense world theory suggests that these social difficulties are caused by sensory hyper-reactivity and sensory overload, rather than empathy impairm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 72 publications
(101 reference statements)
1
2
0
Order By: Relevance
“…Initial empirical evidence yielded that autistic persons "experience overly strong perception, attention, and cognitive evaluation to repetitive expressions, particularly negative emotional expressions. This result supports the intense world theory more strongly than the mindblindness hypothesis" [122].…”
Section: Weak Central Coherence With An Intense World: Do Unusual Exp...supporting
confidence: 79%
“…Initial empirical evidence yielded that autistic persons "experience overly strong perception, attention, and cognitive evaluation to repetitive expressions, particularly negative emotional expressions. This result supports the intense world theory more strongly than the mindblindness hypothesis" [122].…”
Section: Weak Central Coherence With An Intense World: Do Unusual Exp...supporting
confidence: 79%
“…The AQ score is calculated as the sum of the scores for each dimension; higher scores denote higher levels of ATs. The scale has high reliability and validity in existing studies ( Meng et al, 2021 ). In the present study, the Cronbach’s α coefficient of the total scale was 0.785.…”
Section: Methodsmentioning
confidence: 95%
“…Here, we found that increased sensory over-responsivity was related to poorer perspective taking (cognitive empathy) skills in the ASD group and poorer empathic concern (emotional empathy) for the DCD group. Difficulty in cognitive empathy, in particular perspective taking, is a common feature of ASD [ 145 ], and relationships with sensory sensitivities have been previously reported [ 146 ].…”
Section: Discussionmentioning
confidence: 99%